31.2k views
19 votes
F(x)=2x−2

g(x) = −2x + 1

Find f(5) • g(3)

User Shamy
by
5.6k points

2 Answers

9 votes

f(5):-


\\ \rm\rightarrowtail 2(5)-2


\\ \rm\rightarrowtail 10-2


\\ \rm\rightarrowtail 8

g(3)


\\ \rm\rightarrowtail -2(3)+1


\\ \rm\rightarrowtail -6+1


\\ \rm\rightarrowtail -5

So

  • f(5)g(3)=8(-5)=-40
User Brice Rebsamen
by
4.9k points
11 votes

Answer:

-40

Explanation:

Given function: f(x) = 2x - 2

f(5) means: substitute x = 5 into the function:

⇒ f(5) = 2(5) - 2

⇒ f(5) = 10 - 2

⇒ f(5) = 8

Given function: g(x) = -2x + 1

g(3) means: substitute x = 3 into the function:

⇒ g(3) = -2(3) + 1

⇒ g(3) = -6 + 1

⇒ g(3) = -5

Therefore,

f(5) · g(3) = 8 · -5 = -40